Attention-deficit/hyperactivity disorder medication does not alter exercise-induced hypoalgesia following an acute bout of dynamic circuit resistance exercise - Chelsea C. McKean; Brandon A. Baiamonte; Robert R. Kraemer; Daniel B. Hollander (Termedia Publishing House, 2018)
The primary goal of this study was to investigate the effects of attention-deficit/hyperactivity disorder (ADHD) medications on exercise-induced hypoalgesia (EIH), heart rate, and perceived exertion. Thirty college-age students (10 Controls, 10 ADHD diagnosis, and 10 ADHD diagnosis with medications) completed 2 sessions: 1) a maximal testing session and 2) an experimental session consisting of 3 consecutive dynamic resistance exercise circuits comprised of 12 repetitions of 9 exercises at 60% of 1-repetition maximum using a 1:1 work to rest ratio. All participants, regardless of condition (Controls vs. ADHD without medications vs. ADHD with medications), displayed EIH accompanied by an increase in blood lactate, heart rate, and perceived exertion for the duration of the exercise bout. Therefore, the effects of resistance exercise are not altered by ADHD diagnosis or psychostimulant medication use for ADHD. These findings are intriguing given the known ergogenic and hypoalgesic effects of caffeine, a less potent stimulant.